1995
DOI: 10.2337/diacare.18.7.975
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Functional Alterations of the Arterial Wall in IDDM Patients With and Without Microalbuminuria

Abstract: These results confirm a reduced vasodilatory capacity in diabetes mellitus, with a more marked alteration in microalbuminuric diabetic subjects. This reliable, noninvasive evaluation of arterial function is particularly useful for early diagnosis of vascular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 37 publications
7
64
0
4
Order By: Relevance
“…Not surprisingly, rat, STZ, 5-26w Heart serotonin; SNPÖ vitamin E 5-26w (T) SOD (P) Quilley et al, 1996 rat, STZ, 4-6w Heart BK; ARI 4-6w (T) COX blockade (N) Fulton et al, 1996 rat, STZ, 4-6w Kidney ACh;, BK; SNPÖ L-arginine (P) COX blockade (N) negative results were generally obtained in patients with normoalbuminuria and relatively good metabolic control (Smits et al, 1993;Lambert et al, 1996;Enderle et al, 1998). When microalbuminuric patients were included in the study population, impaired endothelium-dependent vasodilatation was consistently reported (Zenere et al, 1995;Clarkson et al, 1996;Lekakis et al, 1997;Arcaro et al, 1999). Studies investigating endothelial function in animal models of type II diabetes are scarce and have yielded con¯icting results.…”
Section: Experimental and Clinical Evidence For The Presence Of Impaimentioning
confidence: 96%
See 1 more Smart Citation
“…Not surprisingly, rat, STZ, 5-26w Heart serotonin; SNPÖ vitamin E 5-26w (T) SOD (P) Quilley et al, 1996 rat, STZ, 4-6w Heart BK; ARI 4-6w (T) COX blockade (N) Fulton et al, 1996 rat, STZ, 4-6w Kidney ACh;, BK; SNPÖ L-arginine (P) COX blockade (N) negative results were generally obtained in patients with normoalbuminuria and relatively good metabolic control (Smits et al, 1993;Lambert et al, 1996;Enderle et al, 1998). When microalbuminuric patients were included in the study population, impaired endothelium-dependent vasodilatation was consistently reported (Zenere et al, 1995;Clarkson et al, 1996;Lekakis et al, 1997;Arcaro et al, 1999). Studies investigating endothelial function in animal models of type II diabetes are scarce and have yielded con¯icting results.…”
Section: Experimental and Clinical Evidence For The Presence Of Impaimentioning
confidence: 96%
“…In one of the few experimental studies where a decreased response to nitrovasodilators was observed, it was preceded by a disturbed response to ACh (Dai et al, 1993). An impaired response to nitrovasodilators was more frequently found in humans (McVeigh et al, 1992;Calver et al, 1992;Zenere et al, 1995;Williams et al, 1996;Clarkson et al, 1996;Lekakis et al, 1997), perhaps due to the more advanced state of the diabetes. In support of this contention, the dilatation to isosorbide dinitrate was decreased in microalbuminuric, but not in normoalbuminuric patients (Lekakis et al, 1997).…”
Section: Mechanisms Of Impaired Endothelium-dependent Vasodilatation mentioning
confidence: 99%
“…In particular, microalbuminuria has been viewed as a marker of vascular dysfunction in both the kidneys and systemic vasculature. 24 Studies in both diabetic 25,26 and nondiabetic 27,28 individuals indicate that elevated urinary albumin excretion is associated with abnormalities in tests of endothelial function. Whether such abnormalities may contribute to hypertension is unknown, although hypertension UACR quartiles are gender specific.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Endothelial dysfunction has consistently been reported in type 2 diabetes [33], in contrast to type 1 diabetes, where only half of the studies have reported it [33]. It has been suggested that dysfunction in endothelialdependent and -independent vasodilatation is a continuum, with people with good glycaemic control and normal albumin excretion at one end, and those with microalbuminuria, poor glycaemic control and long duration of diabetes at the other [33][34][35]. It is not known whether differences in the number of circulating EPCs could explain the gradient in endothelial dysfunction in people with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%